THE EXISTENCE OF INDONESIAN MIGRANT WORKER PLACEMENT AGENCIES IN THE CONSIGNMENT PROCESS OF INDONESIAN MIGRANT WORKERS - Kris Juniansyah; Emelia Kontesa; Amancik Amancik (Bengkoelen Justice : Jurnal Ilmu Hukum, 2023)
The existence of the Indonesian Migrant Worker Placement Agency (known as Perusahaan Penempatan Pekerja Migran Indonesia) is regulated in Law Number 8 of 2017 regarding the protection of Indonesian Migrant Workers. In some cases, many Indonesian Migrant Workers still work abroad non-procedurally or illegally. This study needed to be conducted to investigate the factors that cause many Prospective Indonesian Migrant Workers not willing to join Indonesian Migrant Worker Placement Agency. Therefore, this study is expected to provide scientific benefits for readers and can be used as the material of thought by policymakers. This juridical-empirical research used the interview technique to collect the data as materials to obtain the answers to the research problems. The samples of this study were The Class I Immigration Checkpoint Bengkulu Office, known as Kantor Imigrasi Kelas I TPI Bengkulu, Indonesian Migrant Worker Placement Agency, and Prospective Indonesian Migrant Workers. Some questions were asked directly to the informants to get the descriptions of the existence of Indonesian Migrant Worker Placement Agencies in the consignment process of the Indonesian Migrant Workers. The existence of Indonesian Migrant Worker Placement Agencies in the consignment process of Indonesian Migrant Workers based on Law Number 18 of 2017 has not been actualized optimally due to some problems. The problems included many Indonesian Migrant Workers who worked abroad non-procedurally or illegally, the regulation still needed to be evaluated, and lack of socialization related to the recruitment process of Indonesian Migrant Workers.